Iron vs. ruthenium: syntheses, structures and IR spectroelectrochemical characterisation of half-sandwich Group 8 acetylide complexes. (12th August 2020) - Harrison, Daniel P.; Kumar, Varshini J.; Noppers, Johanna N.; Gluyas, Josef B. G.; Sobolev, Alexandre N.; Moggach, Stephen A.; Low, Paul J.
Abstract : A synthetic 'trick' affording complexes [M(CCR)(dppe)Cp′] (M = Fe, Ru) in high purity directly from the reaction vessel is described. Abstract : A convenient modification to the established synthetic routes for the preparation of complexes [M(CCR)(dppe)Cp′] (M = Fe, Ru; Cp′ = η 5 -C5 H5 (Cp), η 5 -C5 Me5 (Cp*); R = C6 H5, C6 H4 - p -OMe, C6 H4 - p -NO2, t Bu) and [Ru(CCR)(PPh3 )2 Cp] from the corresponding [MCl(PP)Cp′] complex and the alkyne HCCR via an intermediate vinylidene is described. The complexes are generally obtained as high quality crystalline samples directly from the reaction mixture. In agreement with previous studies, the iron complexes undergo a predominantly metal-centred oxidation, whilst there is greater involvement of the acetylide ligand in the oxidation processes associated with the ruthenium analogues. Analysis of the redox properties and spectroelectrochemical investigations reveal limited differences in the gross electronic structures of the Cp vs. Cp* derivatives in each of the Fe and Ru series.